2015
DOI: 10.3389/fpls.2015.00549
|View full text |Cite
|
Sign up to set email alerts
|

Changing environmental conditions and applying organic fertilizers in Origanum vulgare L.

Abstract: Any improvement in agricultural systems that results in higher production should also reduce negative environmental impacts and enhance sustainability. The aim of this research was to investigate the effect of two different production systems, one open-field and the other shade-enclosure with four bocashi doses, in order to find the best environmental option in terms of yield, physiological and morphometric characteristics in one oregano (Origanum vulgare L.) cultivar. In this study a completely randomized blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
0
14
0
2
Order By: Relevance
“…The photosynthetic pigments from the leaves of the three groups were measured (chlorophylls, pheophytins, and carotenoids). Total chlorophylls and carotenoid concentration of the LT group was significantly higher (547.40 and 53.31 µg/g FW, respectively) than in NT group (349.30 and 36.86 µg/g FW, respectively), indicating that the photosynthetic pigment levels might contribute to the difference in the photosynthetic capacity among the temperature conditions [ 17 , 18 ]. In contrast, total content of pheophytins in LT plants remained almost unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…The photosynthetic pigments from the leaves of the three groups were measured (chlorophylls, pheophytins, and carotenoids). Total chlorophylls and carotenoid concentration of the LT group was significantly higher (547.40 and 53.31 µg/g FW, respectively) than in NT group (349.30 and 36.86 µg/g FW, respectively), indicating that the photosynthetic pigment levels might contribute to the difference in the photosynthetic capacity among the temperature conditions [ 17 , 18 ]. In contrast, total content of pheophytins in LT plants remained almost unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies that have applied bokashi to the soil have reported an increase in crop yields (Xu 2001;Zaman et al 2010;Murillo-Amador et al 2015). Nevertheless, few studies have evaluated the relationships between the N availability of bokashi and yield and crop characteristics.…”
Section: Elements Of Soil Fertility Management Inclusion Of the Use mentioning
confidence: 99%
“…In addition, it contributes to the soil with different types of microorganisms, including fungi, bacteria, and actinomycetes, which can improve the health of the soil (Silva et al 2014;Restrepo and Hensel 2015). Therefore, applying bokashi to the soil increases the organic matter content and improves its properties, providing nutrients and reducing nutrient leaching (Murillo-Amador et al 2015). Thus, a widespread use of bokashi could contribute to an increase in the efficiency of crops' use of nutrients, as occurs with the application of compost, which is a common practice in Table 1 Physicochemical parameters of bokashi elaborated with different raw materials Raw materials used to elaborate the bokashi: BPP: Oven-carbonized rice husk, chicken manure, molasses, rice bran, and forest soil BPJ: Chicken manure, coffee pulp, forest soil, and plant waste BAA: Chicken manure, cow manure, burnt rice husk, unprocessed rice husk, chopped banana bunch peduncle, rice bran, materials inoculated with efficient microorganisms, molasses, and water sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Carvacrol and thymol represent the dominant components of the EO and, on the basis of their prevalence, two main chemotypes are commonly attributed to this subspecies: carvacrol-chemotype, typically found in Greece [ 11 , 12 , 13 ] and thymol-chemotype, widespread in Sicily (Italy) and other Mediterranean areas [ 5 , 14 , 15 , 16 ]. Literature highlights that EO quality and quantity are significantly influenced by cultivation practices [ 17 , 18 , 19 , 20 , 21 , 22 ], environmental conditions [ 23 , 24 , 25 , 26 , 27 ] and genetic aspects [ 2 , 27 , 28 , 29 , 30 , 31 ]. Previous studies have focused on assessing the effect of water stress and nitrogen fertilizer on plant growth and yield and on EO yield and quality [ 18 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%